Effects of Stephania hainanensis alkaloids on MSU-induced acute gouty arthritis in mice - Hao-fei Fan; Xing-yue Fang; Hao-lin Wu; Yi-qian Xu; Li-chong Gong; Dao-rui Yu; Hao Jia; Xiao-liang Tang; Qi-bing Liu (BMC, 2021)
Abstract Background Gout is initiated by the precipitation of monosodium urate (MSU) crystals within the joints and soft tissues, and it can eventually cause acute or chronic arthritis. MSU crystals trigger, amplify, and maintain a strong inflammatory response through promoting proinflammatory activity. In this study, the therapeutic effects of Stephania hainanensis (S. hainanensis) total alkaloid (SHA) were tested and evaluated on MSU-induced acute gouty arthritis in a mouse model. Methods After oral administration of SHA (10 or 20 mg/kg) or the antigout medicine colchicine (0.5 mg/kg) once daily for 3 consecutive days, MSU crystals suspended in saline (2.5 mg/50 μl) were intradermally injected into the right paw of the mice. Then, SHA and colchicine were administered for another 2 days. During this period, swelling of the ankle and clinical scores were measured at 12, 24, and 48 h postinjection. After the mice were euthanized, inflammatory cytokine expression and paw tissue inflammation-related gene and protein expression, and a histopathological analysis was performed. Results SHA had obvious therapeutic effects on MSU-induced acute gouty arthritis in mice. SHA alleviated ankle swelling and inhibited the production of cytokines, such as IL-1β and TNF-α. In addition, NLRP3, Caspase-1 and IL-1β, which are activated by MSU were also suppressed by SHA. The histological evaluation showed that SHA relieved the infiltration of inflammation around the ankle. Conclusions These results suggest that SHA is capable of anti-inflammatory activities and may be useful for treating gouty arthritis.